Smart policy toward high-skill emigrants - Michael A. Clemens (IZA World of Labor, 2015)
Immigration officials in rich countries are being asked to become overseas development officials, charged with preventing skilled workers from leaving poor countries, where their skills are needed. Some advocates urge restrictions or taxes on the emigration of doctors and engineers from developing countries. Others urge incentives to encourage skilled workers to remain or return home or policies to facilitate their interactions with home countries. Regulations often reflect compassionate and political sentiments without clear evidence that the regulations achieve the desired development goals and avoid pernicious side effects.
Keywords: F22; J24; O15; 330; development; emigration; training; education; talent; brain drain